Фізичне моделювання гомогенізації сталі при фінішному легуванні у виливниці - Андрюхін, Р. П.; Молчанов, Л. С.; Синегін, Є. В. (Національна металургійна академія України, 2021)
У статті обговорюється технологія фінішного легування сталі при розливанні зверху та сифоном. За рахунок зменшення активності кисню в металі через порівняно нижчу від попередніх етапів сталеплавильного переділу температуру розливки досягається зменшення угару феросплавів та збільшується ступінь засвоєння корисних елементів феросплавів. Ключовим аспектом для досягнення максимальної ефективності розглянутої технології є швидке розчинення феросплавів та рівномірний розподіл легуючих компонентів у металі. Метою цього дослідження є визначення найбільш раціональної з погляду часу усереднення металу за хімічним складом технології введення добавки. Для вирішення поставленої задачі було застосовано метод фізичного моделювання на водній прозорій моделі із використанням флуоресцентного барвника. За результатами серії експериментів було визначено раціональний спосіб розливки та режим введення легуючої добавки для забезпечення найшвидшого її розподілення в металі.

The article describes the method of finish alloying steel in molds in top and bottom casting. Due to the reduction of oxygen activity in the metal due to the relatively lower casting temperature than the previous stages of steelmaking redistribution, it is achieved the reduction of the ferroalloys loss and increasing the yield of useful elements of ferroalloys. An important indicator of the implementation of the proposed technology is the alloying of steel in the mold to obtain steel of a certain brand in small volumes. The aim of the study is to determine the rational place of addition of alloys into the volume of the melt and the method of casting, for the best dissolution of alloys in steel directly in the mold. To solve this problem, the method of physical modeling on a water transparent model using a fluorescent dye that glows brightly in ultraviolet light was used. The experiment consisted of three series of with different methods of casting and introduction of dye: 1) top casting with the introduction of dye into the mold; 2) bottom casting with the introduction of dye into the mold; 3) bottom casting with the introduction of dye in the trumpet. It was analyzed that the averaging of the dye is more efficient at a lower liquid level in the mold, because mixing occurs due to the flow of liquid in the mold, the higher the liquid level in the mold, the weaker the mixing flows. The research revealed minimization of averaging time at the optimal fluid level. For top and bottom casting with the addition of dye to the mold, the optimal level is 33%. When the dye is introduced into the center, there is a slight directly proportional increase in the time of complete homogenization with an increase in the liquid level in the mold. Among the analyzed methods of steel casting, the most effective in terms of homogenization of the alloying additive is bottom casting. The color of the liquid at different stages of filling the mold with the introduction of the dye at the level of 25% of the height of the mold is analyzed.
Physical modeling of steel homogenization during finish alloying in the mold
Keywords: фізичне моделювання; фінішне легування; розливка сталі; гомогенізація; physical modeling; finishing alloying; steel casting; homogenization